The relationship between artificial intelligence and reducing the cognitive load of learners - Haseeb Mohammed Fakih (Zanco Journal of Humanity Sciences)
The research aims to demonstrate the importance of connecting education to technological development, and the process of student use of such technology. The educational institution achieves the specific goals of acquiring skills and knowledge through inputs and in order to reach outputs that make the leaner work smoothly and in an effective and analytical manner and not in the manner of memorization which requires a great time and effort ,and over time the learner is likely to forget it most . Moreover, the use of cognitive intelligence reduces the cognitive burden and allows review a large amount of formation that can be obtained from the computer automatically and quickly so that the learner uses it as information or uses it in analysis and inference.